Integrating Experimental and Computational Insights into D-Amino Acid Inhibition of Aluminum Alloy 7075-T6 Corrosion in Saline Media - Paez-Collio, M; Paez-Collio, M (ELSEVIER SCIENCE SA, 2025)
D-amino acids have emerged as promising eco-friendly corrosion inhibitors due to their biodegradability, low toxicity, and aqueous solubility. In this work, we evaluate the inhibition performance of D-leucine and Dmethionine on aluminum alloy 7075-T6 exposed to a 0.1 M NaCl solution. Density functional theory (DFT) revealed a stronger interaction between D-leucine and the aluminum surface compared to D-methionine, supporting its superior inhibitory behavior. Electrochemical impedance spectroscopy (EIS) results confirmed a significant increase in polarization resistance and impedance values in the presence of D-leucine, with inhibition efficiencies of up to 90 %. In contrast, D-methionine showed limited protection, and its combination with Dleucine did not exhibit a synergistic effect. These findings are supported by polarization studies and surface analysis, highlighting the role of molecular structure and adsorption mechanisms in corrosion inhibition. The integration of experimental and theoretical approaches provides a comprehensive understanding of D-amino acids as sustainable inhibitors for high-strength aluminum alloys.